Sodium Sensitivity, Sodium Resistance, and Incidence of Hypertension: A Longitudinal Follow-Up Study of Dietary Sodium Intervention. Issue 1 (July 2021) - He, Jiang; Huang, Jian-Feng; Li, Changwei; Chen, Jing; Lu, Xiangfeng; Chen, Ji-Chun; He, Hua; Li, Jian-Xin; Cao, Jie; Chen, Chung-Shiuan; Bazzano, Lydia A.; Hu, Dongsheng; et al.
Abstract : Cross-sectional studies have reported that high sodium sensitivity is more common among individuals with hypertension. Experimental studies have also reported various animal models with sodium-resistant hypertension. It is unknown, however, whether sodium sensitivity and resistance precede the development of hypertension. We conducted a feeding study, including a 7-day low-sodium diet (1180 mg/day) followed by a 7-day high-sodium diet (7081 mg/day), among 1718 Chinese adults with blood pressure (BP) <140/90 mm Hg. We longitudinally followed them over an average of 7.4 years. Three BP measurements and 24-hour urinary sodium excretion were obtained on each of 3 days during baseline observation, low-sodium and high-sodium interventions, and 2 follow-up studies. Three trajectories of BP responses to dietary sodium intake were identified using latent trajectory analysis. Mean (SD) changes in systolic BP were −13.7 (5.5), −4.9 (3.0), and 2.4 (3.0) mm Hg during the low-sodium intervention and 11.2 (5.3), 4.4 (4.1), and −0.2 (4.1) mm Hg during the high-sodium intervention ( P <0.001 for group differences) in high sodium-sensitive, moderate sodium-sensitive, and sodium-resistant groups, respectively. Compared with individuals with moderate sodium sensitivity, multiple-adjusted odds ratios (95% CIs) for incident hypertension were 1.43 (1.03–1.98) for those with high sodium sensitivity and 1.43 (1.03–1.99) for those with sodium resistance ( P =0.006 for nonlinear trend). Furthermore, a J-shaped association between systolic BP responses to sodium intake and incident hypertension was identified ( P <0.001). Similar results were observed for diastolic BP. Our study indicates that individuals with either high sodium sensitivity or sodium resistance are at an increased risk for developing hypertension. Abstract : Supplemental Digital Content is available in the text.